Prospective Observational Study of Adverse Drug Reactions of Anti-HER2 and Microtubule Damaging Drugs Used in Cancer Treatment in a Tertiary Care Hospital - Prasannah, Lakshmi; Sathish; Lowrance, Sumi (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Cancer treatment has witnessed remarkable advancements with the development of targeted therapies, such as anti-HER2 agents and microtubule-damaging drugs. Despite their efficacy, these drugs can be associated with a spectrum of Adverse Drug Reactions (ADRs) that may impact patient safety and treatment outcomes. Data on the safety profile of cancer treatment are scarce. Aim This prospective observational study aimed to systematically assess and characterize adverse drug reactions related to anti-HER2 and microtubule-damaging drugs in the clinical setting of a tertiary care hospital. Materials and Methods We conducted a comprehensive observational study over a specified period involving patients undergoing cancer treatment with anti-HER2 and microtubule-damaging drugs. A structured data collection process was employed to record patient demographics, treatment regimens, and observed adverse drug reactions. The severity of adverse drug reactions was categorized according to well-established criteria. The data was analyzed using frequency distribution association analysis to identify potential risk variables for adverse drug reactions. Results and Discussion Preliminary results from our study displayed an extensive array of adverse drug events associated with anti-HER2 and microtubule-damaging drugs, including cardiotoxicity, neuropathy, and myelosuppression. The degree of incidence and impact of adverse drug reactions varied depending on both patient medications and their variables. Furthermore, certain risk factors, such as age, comorbidities, and concomitant medications, were identified as potential predictors of adverse drug reactions. Conclusion This prospective observational study provides valuable insights into the incidence, patterns, and risk factors of ADRs related to anti-HER2 and microtubule-damaging drugs in cancer treatment. The findings will aid healthcare professionals in optimizing treatment strategies, monitoring patients effectively, and managing adverse drug reactions, ultimately providing high-quality care to patients in a tertiary hospital. Advanced research and continuous surveillance are essential to enhance our understanding of these adverse drug reactions and develop strategies for their prevention and management.
Keywords: Adverse drug reactions; Quality; Safety profile on cancer treatment; Patient care